Covalent coupling of myofibrillar protein–6-gingerol: Binding sites, alterations in protein structure and gel properties - Jiamei Li; Geyi Ren; Jiaqi Sun; Fei Li; Hongzhao Zhang; Ping Han; Shiling Lu; Juan Dong (Journal of Food Engineering, 2027)

The role of orbital obliquity in modulating Pliocene warm period climate: An assessment using idealized extreme experiments - Xiaofang Huang; Shiling Yang; Alan Haywood; Julia Tindall; Minmin Sun; Xiaoxiao Yang; Hongmei Li; Wenying Jiang (Global and Planetary Change, 2026)

Effects of eugenol nanoemulsion on histamine accumulation of Xinjiang fermented sausage - Pingcan Li; Honghong Yu; Shiling Lu (Food Control, 2026)

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

Tailoring the structural and textural characteristics of plant-based meat analogues by ice-templating technique - Pan Zhang; Jingwen Sun; Shiling Zhang; Ying Li; Hui Gao; Guowei Shu; Guoliang Li; Xiaolin Yao (Food Research International, 2026)

Metamifop-induced human breast cancer cells proliferation: Revealing a proliferation mechanism distinct from 17β-estradiol - Jingjing Wu; Ya Zhou; Yu Wang; Junqi Zhu; Lu Lin; Huihua Tan; Shiling Liu; Yahui Li; Feng Zhao (Pesticide Biochemistry and Physiology, 2026)

Differential tolerance and response of chain-elongation bacteria and methanogens to undissociated n-octanoic acid: Protective layer, membrane stability, and energy metabolism - Zimu Li; Xiyang Lu; Shiling Xu; Yuhan Wang; Shuang Qiu; Jiawei Bai; Shijian Ge (Bioresource Technology, 2026)

Impact of ultrasound-assisted braising on Xinjiang-style jar stewed mutton flavor compounds - Xinyu Chen; Tengbin Wang; Huabo Fu; Siqi Qiu; Yuhan Duan; Xulong Li; Jingyun Wang; Xin Guo; Shiling Lu (Food Chemistry, 2026)

Codification and research for mass timber buildings in selected seismic regions: An overview - Shiling Pei; Massimo Fragiacomo; Hiroshi Isoda; Minghao Li; Yan Xiao; Tobias Smith (Engineering Structures, 2026)

Enhanced degradation of carbamazepine in water by a chitosan-supported tea polyphenols/nano-zero-valent iron system: Mechanistic insights and toxicological risk assessment - Weiwei Yu; Yuanxin Liu; Jianglin Tan; Yue Liang; Jiang Hu; Qing Tu; Shuo Yang; Ji Li; Sikai Zhao; Yang Liu; Xinyan Li; Yan Luo; et al. (Journal of Cleaner Production, 2025)

Highly efficient degradation of sulfamethoxazole by peroxydisulfate activated with phosphoric acid-modified biochar-supported copper sulfide: Performance, mechanisms, and potential applications - Weiwei Yu; Xiyin Zheng; Xi Chen; Cong Liu; Bolin Li; Lu Lv; Yuanxin Liu; Ji Li; Xinyan Li; Yan Luo; Dan Liu; Shiling Chen (Journal of Environmental Chemical Engineering, 2025)

Dialysis-assisted control significantly enables stable long-term unaerated partial nitrification in a microalgal-bacterial consortium treating hydrolyzed urine - Zimu Li; Zhipeng Chen; Yue Xie; Yanbing Hu; Shiling Xu; Sheng Yu; Shuang Qiu; Shijian Ge (Bioresource Technology, 2025)

The xylem anatomical structure, physiological characteristics and aromatic components analyses explain the difference of fungal solution induced agarwood formation in Aquilaria sinensis - Shengjiang Pang; Weiwei Zhao; Guihua Huang; Qingbin Jiang; Zaizhi Zhou; Qingqing Zhang; Zuwei Tian; Pei Zhang; Zhongguo Li; Shuokun Deng; Shiling Liu; Baoguo Yang (Trees, 2025)

Juvenile hormone signaling regulates apoptosis mediated chlorantraniliprole sensitivity in Spodoptera frugiperda (Lepidoptera: Noctuidae) - Jie Luo; Huili Ouyang; Shiling Liu; Haiyan Wu; Faqian Xiong; Taiyi Yang; Honghong Li; Xuesheng Li (Pesticide Biochemistry and Physiology, 2025)

Study of changes in volatile flavor substances during the processing and storage of mutton ham - Xinyu Chen; Huabo Fu; Siqi Qiu; Yuhan Duan; Xulong Li; Xin Guo; Shiling Lu; Jingyun Wang (Food Research International, 2025)

Acidic-thermal coupled degradation of tylosin by using magnetic sulfonated resins under microwave irradiation - Caitiao Fang; Wei Zhang; Chunmei Wang; Shiling Li; Xiaomin Dou; Jun Liu (Journal of Environmental Sciences, 2025)

Effects of Continuous Grafting on the Growth and Selenium Accumulation Characteristics in the Post-Generations of Tomato - Shiling Meng; Xiaoli Song; Wende Zhou; Juan Huang; Yatian Zhao; Wanjia Tang; Yi Tang; Bo Sun; Huanxiu Li; Zhi Huang (Journal of Soil Science and Plant Nutrition, 2025)

Physiological and genetic responses of Chlorella sp. to nitrite accumulation in microalgal-bacterial consortium with partial nitrification treating municipal wastewater - Mengting Li; Zhipeng Chen; Xiang Li; Sheng Yu; Shiling Xu; Shuang Qiu; Shijian Ge (Water Research, 2025)

Flow law of particles carried by well-flushing fluid in the annulus and prediction of flushing efficiency based on numerical simulation-interpretable machine learning model - Hanxuan Song; Fuli Li; Binru Li; Jixiang Guo; Jiao Li; Shiling Zhang; Zihan Li (Fuel, 2025)

Research on soil heavy metals pollution in major mineral and grain production composite areas: Status - sources - early warning - Yanyan Li; Zhongyi Tian; Pengyan Zhang; Dongfang Zhang; Shiling Tao; Feng Feng; Mingzhou Qin (Journal of Environmental Chemical Engineering, 2025)

Correcting microplastic pollution and risk assessment in Chinese watersheds - Feng Yu; Weiwei Yu; Yan Zhao; Yue Liang; Jiang Hu; Rongqi Liu; Shiling Chen; Qinwei Chen; Yuanxin Liu; Xiyin Zheng; Xinyan Li (Environmental Pollution, 2025)

Comprehensive study of flusulfinam in paddy water–sediment microcosms: Enantioselective fate, degradation pathways, and toxicity assessment - Shiling Liu; Xiaoli Li; Siying Qin; Heng Zhang; Tengfei Zhang; Junqi Zhu; Lu Lin; Lei Lian; Fayang Xie; Huihua Tan; Feng Zhao (Journal of Hazardous Materials, 2025)

Basing target enzyme study the enantioselective bioactivity action mechanism of flusulfinam, a novel HPPD inhibitor herbicide - Shiling Liu; Siying Qin; Tengfei Zhang; Heng Zhang; Junqi Zhu; Xiaoli Li; Yuanfu Li; Feng Zhao (Pesticide Biochemistry and Physiology, 2025)

Advancing detection of fungal and mycotoxins contamination in grains and oilseeds: Hyperspectral imaging for enhanced food safety - Zhen Guo; Jing Zhang; Haifang Wang; Shiling Li; Xijun Shao; Lianming Xia; Ibrahim A. Darwish; Yemin Guo; Xia Sun (Food Chemistry, 2025)

Novel anti-oxidative peptides from equine hemoplasma protein hydrolysates: Purification, identification and protective effects on Caco-2 cells - Zehao Ma; Yuhan Li; Ziqiao Zhao; QianQian Song; Qingling Wang; Shiling Lu; Jingyun Wang (Food Research International, 2025)

Volatile profiles and characteristic odorants in camellia seeds with different heat pretreatments - Shiling Feng; Pingjin Li; Yusong Li; Xinsheng Xiao; Xinyu Chen; Haiqin Leng; Heng Liang; Lijun Zhou; Tao Chen; Chunbang Ding (Food Chemistry, 2025)

Gel properties of sheep's hoof gelatin-dietary polysaccharide interpenetrating polymer network complex gels with application in low fat lamb patties - Yuhan Li; Hongyan Yu; Ziqiao Zhao; Qianqian Song; Zehao Ma; Jingyun Wang; Shiling Lu; Qingling Wang (Food Chemistry, 2025)

Characterization of thyme essential oil microcapsules and potato starch/pectin composite films and their impact on the quality of chilled mutton - Jingyun Wang; Lingrui Li; Yuhan Li; Qianqian Song; Yiqing Hu; Qingling Wang; Shiling Lu (Food Chemistry, 2025)

Effects of glycation modifications of different glycosylating agents on the molecular structure and gel properties of sheep's hoof gelatin - Yuhan Li; Nanqi Li; Qianqian Song; Ziqiao Zhao; Ruyan Yuan; Jingyun Wang; Shiling Lu; Qingling Wang (Food Hydrocolloids, 2025)

Development of a portable multi-step microfluidic device for point-of-care nucleic acid diagnostics - Lulu Shi; Zirui Pang; Jianghao Yu; Jiaming Zhu; Xiaohong Xie; Shiling Xie; Lichuan Gu; Wei Hu; Hai Xu; Ling Li; Jifang Tao; Mingyu Wang (Analytica Chimica Acta, 2025)

A new view into the characterization of dissolved organic matter composition in lakes and traceability studies - Juan Huan; Jialong Yuan; Xiangen Xu; Hao Zhang; Xincheng Li; Wenxin Cai; Shiling Gu; Haoran Ju; Liwan Zhou (Science of The Total Environment, 2024)

Gelatin/polyvinyl alcohol films loaded with doubly stabilized clove essential oil chitosomes: Preparation, characterization, and application in packing marinated steaks - Cenchen Ran; Qingqing Li; Mou Zhao; Haotian Cui; Yi Yang; Kui Diao; Yazhi Liu; Shiling Lu; Juan Dong; Qingling Wang (Food Chemistry, 2024)

Development and characterization of wax–bovine bone protein-grapeseed oil composite oleogels: Experimental and molecular simulation studies - Jingya Chen; Wenjing Shi; Cenchen Ran; Haotian Cui; Yangyang Li; Kui Diao; Shiling Lu; Juan Dong; Qingling Wang (Food Chemistry, 2024)

MicroRNA-451 Regulates Angiogenesis in Intracerebral Hemorrhage by Targeting Macrophage Migration Inhibitory Factor - Shuang Bai; Ge Zhang; Shiling Chen; Xuan Wu; Jiarui Li; Jingxuan Wang; Danyang Chen; Xia Liu; Jiahui Wang; Yuanwei Li; Yingxin Tang; Zhouping Tang (Molecular Neurobiology, 2024)
Intracerebral hemorrhage (ICH) is a subtype of stroke with the highest fatality and disability rate. Up to now, commonly used first-line therapies have limited value in improving prognosis. Angiogenesis is essential to neurological recovery after ICH. Recent studies have shown that microRNA-451(miR-451) plays an important role in angiogenesis by regulating the function of vascular endothelial cells. We found miR-451 was significantly decreased in the peripheral blood of ICH patients in the acute stage. Based on the clinical findings, we conducted this study to investigate the potential regulatory effect of miR-451 on angiogenesis after ICH. The expression of miR-451 in ICH mouse model and in a hemin toxicity model of human brain microvascular endothelial cells (hBMECs) was decreased the same as in ICH patients. MiR-451 negatively regulated the proliferation, migration, and tube formation of hBMECs in vitro . MiR-451 negatively regulated the microvessel density in the perihematoma tissue and affected neural functional recovery of ICH mouse model. Knockdown of miR-451 could recovered tight junction and protect the integrity of blood-brain barrier after ICH. Based on bioinformatic programs, macrophage migration inhibitory factor (MIF) was predicted to be the target gene and identified to be regulated by miR-451 inhibiting the protein translation. And p-AKT and p-ERK were verified to be downstream of MIF in angiogenesis. These results all suggest that miR-451 will be a potential target for regulating angiogenesis in ICH.

Effects of Mutual Grafting on Fruit Quality in Post-grafting generation of Two Genotypes Cherry Tomato (Lycopersicon esculentum) - Zhi Huang; Shiling Meng; Huizhong Luo; Wende Zhou; Juan Huang; Yatian Zhao; Xiaoli Song; Yi Tang; Bo Sun; Huanxiu Li (Journal of Soil Science and Plant Nutrition, 2024)

Enhanced detection of Aspergillus flavus in peanut kernels using a multi-scale attention transformer (MSAT): Advancements in food safety and contamination analysis - Zhen Guo; Jing Zhang; Haifang Wang; Haowei Dong; Shiling Li; Xijun Shao; Jingcheng Huang; Xiang Yin; Qi Zhang; Yemin Guo; Xia Sun; Ibrahim Darwish (International Journal of Food Microbiology, 2024)

Isolation, purification, characterization, and analysis of the antioxidant activity of antioxidant peptides from walnut milk fermented with Lactobacillus paracasei SMN-LBK - Hui Zhong; Baokun Li; Zhexin Fan; Zhifeng Fang; Yuhui Li; Shiling Lu; Yuechenfei Shen; Wenjing Wang; Ruofan Zhang (Food Bioscience, 2024)

Nano zero valent iron stimulated acetaldehyde oxidation, electron transfer, and RBO pathway for enhanced medium-chain carboxylic acids production - Zimu Li; Shuang Qiu; Shiling Xu; Xiyang Lu; Yuhan Wang; Shijian Ge (Water Research, 2024)

Comprehensive study of chiral herbicide flusulfinam uptake, translocation, degradation, and subcellular distribution in rice (Oryza sativa L.) - Shiling Liu; Xiaoli Li; Heng Zhang; Siying Qin; Liying Liang; Ying Liao; Junqi Zhu; Huihua Tan; Feng Zhao (Pesticide Biochemistry and Physiology, 2024)

Assessing the structural and foaming property changes in egg yolk proteins due to malondialdehyde: Experimental and molecular docking studies - Jingya Chen; Jiaxin Jin; Yu Liu; Mengbin Zhao; Zeliang Qi; Wenjing Shi; Yangyang Li; Shiling Lu; Juan Dong; Qingling Wang (Food Chemistry, 2024)

Engineering heterogeneous hierarchical hydrogels based on Artemisia sphaerocephala Krasch polysaccharide/whey protein isolate fibrils aqueous two-phase emulsion - Pan Zhang; Qingxia Gou; Shiling Zhang; Xinyue Mei; Xu Zhao; Guoliang Li; Yapeng Fang; Mouming Zhao; Katsuyoshi Nishinari; Xiaolin Yao (Food Hydrocolloids, 2024)

Dual-aspect attention spatial-spectral transformer and hyperspectral imaging: A novel approach to detecting Aspergillus flavus contamination in peanut kernels - Zhen Guo; Jing Zhang; Haifang Wang; Shiling Li; Xijun Shao; Haowei Dong; Jiashuai Sun; Lingjun Geng; Qi Zhang; Yemin Guo; Xia Sun; Lianming Xia; et al. (Postharvest Biology and Technology, 2024)

Extraction and identification of polyphenol from Camellia oleifera leaves using tailor-made deep eutectic solvents based on COSMO-RS design - Shiling Feng; Guanfeng Deng; Huanyao Liu; Haiqiu Shi; Pingjin Li; Xiao Li; Tao Chen; Lijun Zhou; Ming Yuan; Chunbang Ding (Food Chemistry, 2024)

Coagulation pretreatment coupled with indigenous microalgal-bacterial consortium system for on-site treatment of rural black wastewater - Mengting Li; Zhipeng Chen; Di Zhou; Shiling Xu; Shuang Qiu; Shijian Ge (Science of The Total Environment, 2024)

Bacterial community succession and volatile compound changes in Xinjiang smoked horsemeat sausage during fermentation - Honghong Yu; Pingcan Li; Pengcheng Yin; Jixun Cai; Boyu Jin; Haopeng Zhang; Shiling Lu (Food Research International, 2023)

Correction to: Effects of Dl-3‑n‑butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effects of Dl-3-n-butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Vascular cognitive impairment (VCI) has been one of the major types of cognitive impairment. Blood–brain barrier damage plays an essential part in the pathogenesis of VCI. At present, the treatment of VCI is mainly focused on prevention, with no drug clinically approved for the treatment of VCI. This study aimed to investigate the effects of DL-3-n-butylphthalide (NBP) on VCI rats. A modified bilateral common carotid artery occlusion (mBCCAO) model was applied to mimic VCI. The feasibility of the mBCCAO model was verified by laser Doppler, 13 N-Ammonia-Positron Emission Computed Tomography (PET), and Morris Water Maze. Subsequently, the Morris water maze experiment, Evans blue staining, and western blot of tight junction protein were performed to evaluate the effect of different doses of NBP (40 mg/kg, 80 mg/kg) on the improvement of cognitive impairment and BBB disruption induced by mBCCAO. Immunofluorescence was employed to examine the changes in pericyte coverage in the mBCCAO model and the effect of NBP on pericyte coverage was preliminarily explored. mBCCAO surgery led to obvious cognitive impairment and the decrease of whole cerebral blood flow, among which the blood flow in the cortex, hippocampus and thalamus brain regions decreased more significantly. High-dose NBP (80 mg/kg) improved long-term cognitive function in mBCCAO rats, alleviated Evans blue leakage and reduced the loss of tight junction proteins (ZO-1, Claudin-5) in the early course of the disease, thereby exerting a protective effect on the blood–brain barrier. No significant changes in pericyte coverage were observed after mBCCAO. High-dose NBP improved cognitive function in mBCCAO rats. High-dose NBP protected the integrity of BBB by upregulating TJ protein expression, rather than regulating pericyte coverage ratio. NBP could be a potential drug for the treatment of VCI.

Spatio-temporal distribution patterns and quantitative detection of aflatoxin B1 and total aflatoxin in peanut kernels explored by short-wave infrared hyperspectral imaging - Zhen Guo; Jing Zhang; Haowei Dong; Jiashuai Sun; Jingcheng Huang; Shiling Li; Chengye Ma; Yemin Guo; Xia Sun (Food Chemistry, 2023)

Biodegradation characteristics and mechanism of terbuthylazine by the newly isolated Agrobacterium rhizogenes strain AT13 - Yanmei Liu; Wei Liu; Menghao Li; Shiling Liu; Dingjiao Peng; Feng Zhao; Xiaogang Wu; Huihua Tan (Journal of Hazardous Materials, 2023)

Effectively facilitating the degradation of chloramphenicol by the synergism of Shewanella oneidensis MR-1 and the metal-organic framework - Xin Li; Shiling Zheng; Yinhao Li; Jiawang Ding; Wei Qin (Journal of Hazardous Materials, 2023)

Construction of a dynamic model to predict the growth of Staphylococcus aureus and the formation of enterotoxins during Kazak cheese maturation - Huixue Cai; Sijie Pei; Yan Zhang; Rongrong Liu; Shiling Lu; Baokun Li; Juan Dong; Qingling Wang; Xinrong Zhu; Hua Ji (Food Microbiology, 2023)

Microbial degradation of petroleum characteristic pollutants in hypersaline environment, emphasizing n-hexadecane and 2,4 di-tert-butylphenol - Shiling Liu; Wenjiao Yuan; Xiaolin Yang; Chengbin Li; Yishan Ji; Xin Feng; Meitong Li; Yuhong Xie (Environmental Monitoring and Assessment, 2023)

Enhanced hydrolytic removal of tylosin in wastewater using polymer-based solid acid catalysts converted from polystyrene - Shiling Li; Shuhan Sun; Fei Qi; Xiaomin Dou (Journal of Environmental Sciences, 2023)

Effects of fabrication of conjugates between different polyphenols and bovine bone proteins on their structural and functional properties - Li Pan; Jingya Chen; Huihui Fu; Niannian Wang; Junrong Zhou; Shuyao Zhang; Shiling Lu; Juan Dong; Qingling Wang; Haiyan Yan (Food Bioscience, 2023)

A novel Stauntonia leucantha fruits arabinogalactan: isolation and structural characterization - Hui Li; Tao Gao; Zhonghao Zhang; Jiangping Lei; Junchao Hu; Zizhong Tang; Shiling Feng; Chunbang Ding; Tao Chen; Yanger Chen; Shu Yuan; Ming Yuan (Carbohydrate Polymers, 2023)

Impact of Coreopsis tinctoria Nutt. Essential oil microcapsules on the formation of biogenic amines and quality of smoked horsemeat sausage during ripening - Yazhuo Li; Yukun Geng; Di Shi; Ruiting Li; Juan Tang; Shiling Lu (Meat Science, 2023)

Fosthiazate exposure induces oxidative stress, nerve damage, and reproductive disorders in nontarget nematodes - Shiling Liu; Qiqi Wu; Yanru Zhong; Zongzhe He; Zhen Wang; Rui Li; Minghua Wang (Environmental Science and Pollution Research, 2022)

Antioxidant effect of hawk tea extracts on camellia oil oxidation during microwave heating - Zhou Xu; Xu Li; Shiling Feng; Jing Liu; Lijun Zhou; Ruiwu Yang; Chunbang Ding (Journal of Consumer Protection and Food Safety, 2018)

Comparative transcriptomic insights into the mechanisms of electron transfer in Geobacter co-cultures with activated carbon and magnetite - Shiling Zheng; Fanghua Liu; Meng Li; Leilei Xiao; Oumei Wang (Science China Life Sciences, 2018)

C and N stable isotope analysis of human and animal bones at the Beiqian site - Fen Wang; YanBo Song; BaoShuo Li; Rong Fan; GuiYun Jin; ShiLing Yuan (Science China Earth Sciences, 2014)